On Free Trade Agreements (FTAs): the Philippine Perspective - Erlinda M. Medalla; Melalyn C. Mantaring (Philippine Institute for Development Studies (PIDS), 2009)
The formation of free trade agreements (FTAs) has been set in motion worldwide and its conclusion does not appear imminent in the near future. In the face of such developments, the Philippines is hard pressed to formulate a more rational FTA policy framework to deal with not just external, but perhaps more importantly, domestic repercussions. Like any other country, it would have to examine closely the motivations and impact, assess capacity needs, and balance short-term adjustments with long-term opportunities. It would need to look further ahead and formulate a vision about its regional and global participation. This short paper is an attempt to contribute toward this end. It starts with a brief discussion on current developments in Philippine FTA engagement. A suggested framework for FTA policy follows, with some discussion on the noodle bowl syndrome. The paper concludes with a discussion on the prospects for an East Asian FTA.
Keywords: 330; regional trade agreement; preferential trading arrangements (PTAs); East Asian integration; free trade agreements (FTAs); Freihandelszone; Handelspräferenzen; Philippinen; Regionale Wirtschaftsintegration; ASEAN-Staaten